The Influence of The Student Facilitator and Explaining Model in Differentiating IPAS Learning in The Independent Curriculum in Primary Schools - Prihantini; Muhammad Iqbal; Loso Judijanto; Muhammad Sukron Fauzi; Andiopenta; Gingga Prananda (Postgraduate, University of Mataram, 2024)
Science is a combination of Natural Sciences (IPA) and Social Sciences (IPS) which is now a new subject in the Independent Curriculum. Science and Technology began to be taught in elementary schools to develop students' basic abilities in natural sciences and social sciences. In science and science subjects, teachers are still monotonous or too often rely on student books and teacher books. As we know, elementary school students are still children, so if the teacher is always monotonous teaching will be boring. This research aims to determine the effect of the Facilitator and Explain learning model on the science learning outcomes of class IV students at SDN Cibiru 6 KCKB. This type of research is experimental research. The sampling technique uses Purposive Sampling. The instrument in this research is a test of student learning outcomes, while the data analysis technique uses the t-test. Based on the results of the research, the average value of the experimental class was 83.00 and 73.40 in the control class. It can be seen from the results of the data analysis that has been carried out that t count (3.29) > t table (1.68), so the hypothesis is accepted. From the research results it can be concluded that there is an influence of the Facilitator and Explaining model on students' science learning outcomes. For this reason, it is recommended that teachers who teach science subjects apply the Facilitator and Explaining model in the learning process.